Instructors’ Perceptions of the Training Courses Related to Technology in Saudi Universities - Alharbi, Omran Ammar; Alshahrani, Razan Saad Ali (Advances in Social Sciences Research Journal, 2023)
The focus of this paper in on the training that related to the adoption of technology in teaching approaches by educators in one Saudi University. Currently, there are several training courses have provided by institutions to their instructors in Saudi Arabia universities, however, there is insufficient research was carried out by researchers in order to investigate the stakeholders’ perceptions of this workshops. As a result, this study came to examine teacher’s opinion of the raining that provided to the them by one Saudi University as the results of this study might help to address the issues that educators encounter when the attaining training courses. This study used questionnaire for collecting the data from participants. The study sample consisted of 60 participants. The study findings mentioned that educators needs sufficient training courses and based on their needs. Also, The study findings indicated that there is overlapping between the instructors schedules and the time of the workshops.